COGNITIVE PROBLEMS IN SIMULTANEOUS INTERPRETATION - Orunbayeva , Uminiso Sharabidinovna (Educational Research in Universal Sciences, 2024)
Synchronous translation, a remarkable linguistic skill enabling real-time interpretation of spoken or signed language, presents a unique set of cognitive challenges for translators. This scientific article delves into the intricacies of cognitive processes involved in synchronous translation, highlighting key challenges and proposing avenues for future research. By examining cognitive load, working memory, attention management, and the impact of expertise, we aim to deepen our understanding of the cognitive dimensions of synchronous translation.